Approach on the electrochemical reactivity of poly-L-Glutamic acid against doxorubicin and its application in the development of a voltammetric sensor - dos Santos, Daniela Pereira [UNESP]; Bergamini, Márcio Fernando; Zanoni, Maria Valnice Boldrin [UNESP] (My University, 2010)
The poly-L-glutamic acid (PGA), was used a biodegradable polymers as conjugated to doxorubicin (DXR) and also in the modification glassy carbon electrode. The interaction operate via terminal amino groups of the drug and the side chain carboxyl groups of branched PGA film and it is the base to develop a simple voltammetric sensor for the determination of doxorubicin in human urine. The preconcentration of DXR on the modified electrode occurs under open circuit and studied by the methods of square wave voltammetry to monitor the drug. Standard curves were linear over the concentration range of 2.20 - 44.5 μmol L-1 giving a detection limit of 0.45 μmol L-1 show that the proposed sensor is suitable for doxorubicin determination in real samples. © 2010 by ESG.
Keywords: Adsorption; Doxorubicin; Poly-L-glutamic acid; Semiquinone free radical; Urine